Employers’ Needs and Expectations for Qualified Employees (Case Study on the Opinions in One of the Regions in Latvia) - Sloka, Biruta; Kantāne, Ināra; Buligina, Ilze; Tora, Ginta; Dzelme, Juris; Buševica, Regīna; Buligina, Alise; Tora, Pēteris (Economics and Business, 2015)
Qualified, loyal and motivated employees are highly demanded by employers and business promoters. The paper deals with employers’ needs and expectations for qualified and loyal employees, and investigates cooperation of employers, educators and municipalities. The following methods were used: analysis of scientific publications; focus group discussions; surveys of employers, teaching staff, students and graduates of VEI. For survey data analysis descriptive statistical analysis, non-parametric statistical test of Kruskal-Wallis and factor analysis were applied. The main findings indicate that besides professional skills and competence, social competence, motivation to work and responsibility are requested as well.